Establishment and Application of a Method for the Determination of Ganoderic Acid A. (30th November 2020) - Li, Shengyun; Yuan, Yaowu; Yu, Chenchen; Gao, Hao; Tan, Jianxin; Tian, Yiling
Abstract : A method for the quantitative determination of ganoderic acid A was constructed using the principle of indirect competitive enzyme-linked immunosorbent assay (ELISA), and this method was used to determine the ganoderic A contents of Ganoderma lucidum samples in the market. The conjugate of ganoderic acid A and bovine serum albumin was used for four rounds of immunization on test rabbits to obtain rabbit antiganoderic acid A antibody IgG. The enzyme-labeled plate was coated with the conjugate of ganoderic acid A and ovalbumin. The first stage reaction in the indirect competitive ELISA was that the conjugate of ganoderic acid A in the sample competed with the conjugate coated on the enzyme-labeled plate to bind rabbit antibodies. The second stage reaction was the combination of goat anti-rabbit IgG–horseradish peroxidase and rabbit antiganoderic acid A antibody IgG. The results of the determination of ganoderic acid A standard by this method showed that the coefficient of variation of repeated wells in the group was <5%, the detection limit of ganoderic acid A was 0.6 μ g/L, and ganoderic acid A had a substantial dose-response relationship in the content range of 0.9–72.9 μ g/L ( R 2 = 0.994). This method was used to measure the ganoderic A content of 12 varieties of G. lucidum in the market and showed the obvious differences in the ganoderic acid A contents of the different varieties. This method is simple, fast, and of great importance to the quality control of Ganoderma products.